Optimal Contracting with Verifiable Ex Post Signals - Anke Kessler; Christoph Lülfesmann; Patrick Schmitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
We study an adverse selection problem in which information that is imperfectly correlated with the agent's type becomes public ex post. Unbounded penalties are ruled out by assuming that the agent is wealth constrained. The following conclusions emerge. If the agent's utility is increasing in the contractual action (e.g. the quantity traded), the downward distortion in bad states may be strengthened. Hence, ex post information can reduce efficiency. In contrast, if the agent's utility is decreasing in the action level, there may be an upward distortion. Moreover, his rent may increase due to the ex post signal about his type. The qualitative results thus differ substantially depending on the specific situation under consideration, e.g., whether the agent is in a `buyer' or `seller' position. In both cases, however, additional information need not improve the efficiency of the relationship.
Keywords: D82; 330; Adverse Selection; Ex Post Information; Wealth Constraints; Upward Distortion